PRINCIPLES OF NATURE IN EDUCATION - Saidov Bakhtiyor Muhammadievich (American Journals, 2024)
The development of education in Russia in recent years has become one of the priority areas of government activity. Modernization of education, training and upbringing is carried out in accordance with the general trends of the global pedagogical process. The 21st century is the century of human-centric positions, the humanization of relationships, the development of the creative abilities of the individual, and the disclosure of his potential. The focus of national pedagogy is a unique personality who strives for the maximum realization of his capabilities.
Keywords: Pedagogy, attention, principle, condition, creation, personality.